Sugar feeding in triatomines: a new perspective for controlling the transmission of Chagas disease - Costa, Mariana C.; Moreira, Carlos J. C.; Oliveira, Pedro Lagerblad de; Juberg, José; Castro, Daniele Pereira de; Genta, Fernando Ariel (Frontiers in Physiology, 2024)
Triatomines are vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. Currently, there is no vaccine against this disease. Thus, control of the insect vector population is the main strategy available to reduce the number of cases. Triatomines are considered obligate hematophagous, but different alternative feeding behaviors were described, such as haemolymphagy or plant feeding. To determine the preference for sugar feeding in nymphs and adults of Rhodnius prolixus, the insects were exposed a piece of cotton containing bromophenol blue plus sucrose. In addition, we offered several sugars for different species of triatomines, and tested sugar meals as a route of delivery of insecticides in first-instar nymphs of R. prolixus. The effect of sugar feeding on the physiology of these different species of triatomines was recorded. First instar nymphs ingested sucrose more strongly than other stages, and showed high mortality rates. In different species of triatomines, sucrose induced an ingestion, but engorgement varied according to the species. R. prolixus nymphs showed an indiscriminate intake of various sugars, with very different physiological effects. Furthermore, ingesting different combinations of insecticides + sugar significantly reduced insect survival. In summary, we described for the first-time sugar feeding as a widespread behavior in several species of triatomines, and the possibility of the use of toxic sugar baits for the control of these vectors. The knowledge of feeding behavior in these insects can be fundamental for the development of new strategies to control Chagas disease.